Blended Learning in the Digital Era: An Analysis of Self-Regulated Learning Assisted with Edmodo-GeoGebra - Nasrullah, Anton; Marlina, Mira; Ratnasari, Silvia; Hilman, Hilman; Mulyawan, Galuh; Ali , Ashraf (International Journal of Geometry Research and Inventions in Education, 2024)
This study aims to describe students' self-regulated learning in mathematics learning supported by Edmodo-GeoGebra on the topic of the volume of rotating objects. The research employs a qualitative approach with a descriptive method. The participants in this study were 36 students from Universitas Bina Bangsa. The data collection technique involved distributing a self-regulated learning questionnaire consisting of 30 statements with 8 indicators. Data analysis was conducted by calculating the percentage of students' responses, which were then described using percentage interpretation criteria. The analysis results for each indicator of self-regulated learning are as follows: 1) learning initiative 76%; 2) diagnosing learning needs 78%; 3) setting learning goals 76%; 4) viewing difficulties as challenges 75%; 5) utilizing and seeking relevant resources 74%; 6) selecting and applying learning strategies 77%; 7) evaluating the learning process and outcomes 76%; 8) self-concept 74%. The overall average of students' self-regulated learning supported by Edmodo-GeoGebra was 75.57%, categorized as high. This study recommends that educational institutions support and optimize the improvement of students' self-regulated learning.